Modeling hemoglobin and hemoglobin:haptoglobin complex clearance in a non-rodent species–pharmacokinetic and therapeutic implications - Boretti, Felicitas S.; Baek, Jin Hyen; Palmer, Andre F.; Schaer, Dominik J.; Buehler, Paul W. (Frontiers in Physiology, 2014)
Preclinical studies suggest that haptoglobin (Hp) supplementation could be an effective therapeutic modality during acute or chronic hemolytic diseases. Hp prevents Hb extravasation and neutralizes Hb’s oxidative and NO scavenging activity in the vasculature. Small animal models such as mouse, rat and guinea pig appear to be valuable to provide proof-of-concept for Hb neutralization by Hp in diverse pre-clinical conditions. However, these species differ significantly from human in the clearance of Hb:Hp complexes, which leads to long persistence of circulating Hb:Hp complexes after administration of human plasma derived Hp. Alternative animal models must therefore be explored to guide pre-clinical development of these potential therapeutics. In contrast to rodents, dogs have high Hp plasma concentrations comparable to human. In this study we show that like human macrophages, dog peripheral blood monocyte derived macrophages express a glucocorticoid inducible endocytic clearance pathways with a high specificity for the Hb:Hp complex. Evaluating the Beagle dog as a non-rodent model species we provide the first pharmacokinetic parameter estimates of free Hb and Hb:Hp phenotype complexes. The data reflect a drastically reduced volume of distribution (Vc) of the complex compared to free Hb, increased exposures (Cmax and AUC) and significantly reduced total body clearance (CL) with a terminal half-life (t1/2) of approximately 12 hours. Distribution and clearance was identical for dog and human Hb (±) glucocorticoid stimulation and for dimeric and multimeric Hp preparations bound to Hb. Collectively, our study supports the dog as a non-rodent animal model to study pharmacological and pharmacokinetic aspects of Hb clearance systems and apply the model to studying Hp therapeutics.